Exploring the experiences of paid mathematics apprentice teachers: A qualitative investigation - Waddell, Jr, Glenn; Quinn, Robert J.; Acharya, Bibek (American Journal of STEM Education, 2025)
This qualitative study on the experience of paid Apprentice Teachers (ATs) from a UTeach replication program suggests that creating a strong social sense of belonging for Apprentice Teachers is critically important, as is identifying a high-quality mentor teacher in the content area. Additionally, university programs should revise their curricula to address specific topics that are critical to success during Apprentice Teaching, particularly before the culminating semester. Ultimately, the implementation of these recommendations could lead to better teacher retention rates in this population.